Galectin-3, histone deacetylases, and Hedgehog signaling: Possible convergent targets in schistosomiasis-induced liver fibrosis. - Felipe Leite de Oliveira; Katia Carneiro; José Marques Brito; Mariana Cabanel; Jonathas Xavier Pereira; Ligia de Almeida Paiva; Wingkin Syn; Neil C Henderson; Marcia Cury El-Cheikh (Public Library of Science (PLoS), 2017)
Schistosomiasis affects approximately 240 million people in the world. Schistosoma mansoni eggs in the liver induce periportal fibrosis and hepatic failure driven by monocyte recruitment and macrophage activation, resulting in robust Th2 response. Here, we suggested a possible involvement of Galectin-3 (Gal-3), histone deacetylases (HDACs), and Hedgehog (Hh) signaling with macrophage activation during Th1/Th2 immune responses, fibrogranuloma reaction, and tissue repair during schistosomiasis. Gal-3 is highly expressed by liver macrophages (Kupffer cells) around Schistosoma eggs. HDACs and Hh regulate macrophage polarization and hepatic stellate cell activation during schistosomiasis-associated fibrogenesis. Previously, we demonstrated an abnormal extracellular matrix distribution in the liver that correlated with atypical monocyte-macrophage differentiation in S. mansoni-infected, Gal-3-deficient (Lgals3-/-) mice. New findings explored in this review focus on the chronic phase, when wild-type (Lgals3+/+) and Lgals3-/- mice were analyzed 90 days after cercariae infection. In Lgals3-/- infected mice, there was significant inflammatory infiltration with myeloid cells associated with egg destruction (hematoxylin and eosin staining), phagocytes (specifically Kupffer cells), numerically reduced and diffuse matrix extracellular deposition in fibrotic areas (Gomori trichrome staining), and severe disorganization of collagen fibers surrounding the S. mansoni eggs (reticulin staining). Granuloma-derived stromal cells (GR cells) of Lgals3-/- infected mice expressed lower levels of alpha smooth muscle actin (α-SMA) and eotaxin and higher levels of IL-4 than Lgals3+/+ mice (real-time PCR). The relevant participation of macrophages in these events led us to suggest distinct mechanisms of activation that culminate in defective fibrosis in the liver of Lgals3-/- infected mice. These aspects were discussed in this review, as well as the possible interference between Gal-3, HDACs, and Hh signaling during progressive liver fibrosis in S. mansoni-infected mice. Further studies focused on macrophage roles could elucidate these questions and clear the potential utility of these molecules as antifibrotic targets.